The microbiota: a key regulator of health, productivity, and reproductive success in mammals - Khan, Ibrar Muhammad; Nassar, Nourhan; Chang, Hua; Khan, Samiullah; Cheng, Maoji; Wang, Zaigui; Xiang, Xun (Frontiers in Microbiology, 2024)
The gut microbiota, intensely intertwined with mammalian physiology, significantly impacts health, productivity, and reproductive functions. The normal microbiota interacts with the host through the following key mechanisms: acting as a protective barrier against pathogens, maintain mucosal barrier integrity, assisting in nutrient metabolism, and modulating of the immune response. Therefore, supporting growth and development of host, and providing protection against pathogens and toxic substances. The gut microbiota significantly influences brain development and behavior, as demonstrated by comprehensive findings from controlled laboratory experiments and human clinical studies. The prospects suggested that gut microbiome influence neurodevelopmental processes, modulate stress responses, and affect cognitive function through the gut-brain axis.Microbiota in the gastrointestinal tract of farm animals break down and ferment the ingested feed into nutrients, utilize to produce meat and milk. Among the beneficial by-products of gut microbiota, short-chain fatty acids (SCFAs) are particularly noteworthy for their substantial role in disease prevention and the promotion of various productive aspects in mammals. The gut microbiota plays a pivotal role in the reproductive hormonal systems of mammals, boosting reproductive performance in both sexes and fostering the maternal-infant connection, thereby becoming a crucial factor in sustaining mammalian existence. The gut microbiota is a critical factor influencing reproductive success and production traits in mammals. A well-balanced microbiome improves nutrient absorption and metabolic efficiency, leading to better growth rates, increased milk production, and enhanced overall health. Additionally, it regulates key reproductive hormones like estrogen and progesterone, which are essential for successful conception and pregnancy. Understanding the role of gut microbiota offers valuable insights for 3 optimizing breeding and improving production outcomes, contributing to advancements in agriculture and veterinary medicine.This study emphasizes the critical ecological roles of mammalian microbiota, highlighting their essential contributions to health, productivity, and reproductive success. By integrating human and veterinary perspectives, it demonstrates how microbial communities enhance immune function, metabolic processes, and hormonal regulation across species, offering insights that benefit both clinical and agricultural advancements.